The effect of institutional ownership on capital structure of listed firms in Singapore - De Jong, Ethan Felix (Nanyang Technological University, 2020)
Our paper is a contribution to the current understanding of trade-off theory, which states the firms’ optimal choice of capital structure is one that balances the benefit of the tax shield generated by debt and the cost of financial distress. We chose to examine how different proportions of institutional holdings affect the level of debt held by companies. This is based on the assumption that increased institutional ownership would improve corporate governance, which ultimately lowers the cost of financial distress and allows firms to undertake higher levels of debt. We therefore aim to answer the research question: What is the impact of having a larger proportion of institutional investors on the capital structure decisions of firms in Singapore? To answer this question, we utilized a random sample of 305 firms that are listed on the Singapore Exchange, to analyze specific firm characteristics. A First-Difference (FD) regression model was employed to test our hypothesis and study the mechanisms affecting the capital structure. Our findings corroborate those of other academics, who have also found that institutional ownership has a negative or negligible effect on the capital structure of firms, contrary to trade-off theory. Even after further robustness checks, our results still remain unchanged which suggests the presence of other external factors influencing the capital structure decision.